PENGARUH KOMITMEN ORGANISASIONAL, LINGKUNGAN KERJA, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN KOPERASI PASAR SRINADI - Meriandayani, Ni Wayan; Subudi, Made (E-Jurnal Manajemen; Vol 8 No 11 (2019)DO - 10.24843/EJMUNUD.2019.v08.i11.p15, 2019)
Turnover intentions are the desire to move, not yet at the realization stage, namely moving from one workplace to another. The factors that cause turnover intention include work environment, job satisfaction, and organizational commitment. The purpose of this study is to examine the effect of organizational commitment, work environment, and job satisfaction on turnover intention. This research was conducted on employees of Koperasi Pasar Srinadi Klungkung. The population in this study were 298 and sample of 75 respondents was obtained through a proportionate random sampling. Methods of collecting data through interviews and questionnaires. The data analysis technique used is Multiple Linear Regression Analysis. The results showed that the variables of organizational commitment, work environment, and job satisfaction negatively and significantly affected the turnover intention of the Koperasi Pasar Srinadi Klungkung employees. The high organizational commitment, work environment, and job satisfaction in the company can reduce employee turnover intention. Keywords: organizational commitment, work environment, turnover intention, job satisfaction